Contribuições dos estudos de perfil dos graduandos: o caso dos cursos de licenciatura e bacharelado em Química da UNESP/Araraquara - Massi, Luciana [UNESP]; Villani, Alberto (My University, 2014)
This paper focuses on the profile of students of bachelor and teacher training degree in Chemistry and UNESP/Araraquara. Statistical and comparatives analyzes were performed with a large amount of quantitative data on those who registered and passed the entrance examinations of these courses. This information was interpreted based on the concepts of economic and cultural capital developed by Pierre Bourdieu. The first analysis concerned the approval in entrance exams and brings important conclusions regarding the aspects that favor entering university: confirmation of "preparation courses effect"; major weight of cultural capital in relation to economic capital; and observation of the phenomenon of self-selection in relation to the bachelor's under graduation course. The second analysis points to important differences in the profile of a group of students that could be considered homogeneous due to the choice of chemistry course. In addition to bringing new information on the profile of students of chemistry, our analysis has the merit of translating and quantitatively reveals ideas conveyed in common sense about passing the entrance exam.

Este trabalho tem como foco o perfil dos estudantes dos cursos de bacharelado e licenciatura em Química da UNESP/Araraquara. Realizamos análises estatísticas e comparativas com um grande volume de dados quantitativos sobre os inscritos e aprovados no vestibular desses cursos. Interpretamos essas informações com base nos conceitos de capital cultural e econômico desenvolvidos por Pierre Bourdieu. A primeira análise diz respeito à aprovação no vestibular e traz conclusões importantes quanto aos aspectos que favorecem o ingresso na universidade: confirmação do “efeito cursinho”; maior peso do capital cultural em relação ao capital econômico; e observação do fenômeno da auto-seleção em relação ao curso de bacharelado. A segunda análise aponta para importantes diferenciações de perfil em um grupo de estudantes que poderia ser considerado homogêneo em função da opção pela Química. Além de trazer informações novas sobre o perfil dos alunos de Química, nossa análise tem o mérito de traduzir e revelar quantitativamente ideias veiculadas no senso comum sobre a aprovação no vestibular.
Contributions from profile studies of undergraduates: the case of undergraduate programs in Chemistry from UNESP/Araraquara
Keywords: Student’s profile; Socio-economic profile; Higher education; Perfil dos estudantes; Perfil socioeconômico; Ensino Superior